Assessment of health education on knowledge regarding oral antidiabetic drug adherence in urban area, Bengaluru - Ramegowda, Chethana; Hulugappa, Lakshmi (International Journal Of Community Medicine And Public Health, 2019)
Background: Diabetes mellitus is a chronic disease with a high mortality and morbidity. Knowledge regarding the disease is required for the management of drug adherence in diabetes, hence the present study was taken to assess the effectiveness of health education on knowledge regarding oral anti-diabetic drug adherence. Methods: The study was conducted at urban health training centre of a medical college, Bengaluru from October 2015 to July 2016. A total of 70 type 2 diabetes mellitus patients were involved in this descriptive and interventional study. The study subjects included only on oral anti-diabetic drugs and willing to give informed consent. A pre-tested semi-structured proforma was administered and information about socio-demographic profile, and impact of health education intervention on knowledge was obtained. Results: Most of the subjects were female (80%), in the age group of 35-45 years (34%), illiterate (40%), unemployed (67%) with class IV (78%) socio-economic status according to Modified Kuppuswamy classification 2014. The mean±SD age was 52.47±11.06 years. Significant improvement in knowledge regarding adherence to oral anti-diabetic medication was found in study subjects following health education intervention. Conclusions: The study revealed that health education regarding the importance of drug adherence is needed in study subjects and there was significant improvement in knowledge after health education.